Secondary term formation within the EU: term transfer, legal transplant or approximation of Member States' legal systems? - Katia Peruzzo (JoSTrans: The Journal of Specialised Translation)
The EU legal system and the legal systems of its Member States have to adapt to the ever-changing nature of society and are therefore in a constantly evolving state. The EU, which is characterised by a unique lawmaking system, has proved to be an inexhaustible source of legislation, giving rise to a dynamic legal context. The same dynamicity can be observed also from a linguistic perspective. Due to the multilingualism principle, which makes multilingual communication a mandatory activity in EU institutions, new EU legislation and, consequently, new legal concepts are expressed in equally authentic texts. As a result, 23 different varieties of national official languages are being developed within the EU and existing terms are already undergoing a Europeanisation process. This paper presents a case study conducted on the terminology extracted from a corpus of parallel EU documents in English and Italian on the specific subdomain of the standing of victims in criminal proceedings and victims' rights, and discusses the consequences of concept transfer between legal systems within a multidimensional context and in terms of monolingual and multilingual secondary term formation.